2021
DOI: 10.2478/jtim-2021-0035
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between homocysteine levels and post-stroke cognitive impairment in female and male population: from a prospective multicenter study

Abstract: Background and Objectives: To investigate the relationship between homocysteine levels and post-stroke cognitive impairment (PSCI) in Chinese female and male populations with minor acute ischemic stroke or transient ischemic attack. Materials and methods: A total of 1070 participants with clinically confirmed acute minor ischemic stroke or transient ischemic attack and baseline homocysteine information from a nationwide multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In society, robust social support provides individuals with additional resources and encourages the adoption of coping strategies. In particular, although homocysteine was not shown to be a meaningful predictor in regression analysis, a prospective study 47 found that elevated homocysteine levels were independently positively associated with depression or vascular dementia in women with mild acute ischemic stroke or TIA. Thus, future research should examine homocysteine levels as biochemical biomarkers for indicating a risk for low resourcefulness.…”
Section: Discussionmentioning
confidence: 93%
“…In society, robust social support provides individuals with additional resources and encourages the adoption of coping strategies. In particular, although homocysteine was not shown to be a meaningful predictor in regression analysis, a prospective study 47 found that elevated homocysteine levels were independently positively associated with depression or vascular dementia in women with mild acute ischemic stroke or TIA. Thus, future research should examine homocysteine levels as biochemical biomarkers for indicating a risk for low resourcefulness.…”
Section: Discussionmentioning
confidence: 93%
“…In brief, multiple molecular mechanisms underlying Hcy may contribute to the occurrence and development of CVD, including damaging vascular endothelial cells, promoting vascular smooth muscle cell proliferation and migration, and activating excessive oxidative stress reactions, lipid metabolism disorders, and coagulation dysfunction [ 29 ]. Numerous studies have demonstrated that increased plasma Hcy may bring about cardio- and cerebrovascular diseases, neurological disorders, and even target organ damage [ 30 , 31 , 32 , 33 ]. This association between elevated Hcy levels and higher CV mortality was similar in both Korean [ 24 ] and Japanese [ 34 ] general populations, which confirms that the association between them is robust and consistent in East Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that there is an early risk of re-occlusion in patients with large-vessel occlusion stroke associated with intracranial atherosclerotic stenosis [18]. Intravenous injection of tirofiban reduces the rate of early reocclusion without increasing the risk of substantial hemorrhage, symptomatic bleeding, 90-day favorable outcomes, or death rate [19].…”
Section: Discussionmentioning
confidence: 99%